Taurine is an effective therapy against thiram induced tibial dyschondroplasia via HIF-1α/VEGFA and β-catenin/ GSK-3β pathways in broilers - Yanmei Ding (Elsevier, 2021)
Thiram causes tibial dyschondroplasia in broilers, leading to a significant economic loss in the poultry industry. Our study explored the effects of taurine in thiram induced tibial dyschondroplasia (TD) through in vivo and in vitro approches. In in vivo study, thiram resulted in lameness disorder, low production parameters ALP, ACP, and a high level of NOS. While, the taurine exhibited promising effect by reducing lameness, increasing ALP, ACP levels, and significantly lowering NOS level with the restoration of the growth plate. In vitro study, thiram caused distortion and disintegration of chondrocytes. The CCK-8 technique revealed the lower cell activity in TD as compared with the treatment group. Even, the treatment and taurine groups had higher cell activity than control group. Also, the chondrocyte morphology progressively reverted to normal after taurine treatment. It might effectively decrease the symptoms of TD in broilers and their production performance. Further research found that the taurine effectively improved chondrocytes' cell viability and recovered lameness disorder by regulation of HIF-1α, VEGFA, and Wnt/β-catenin signaling pathways. In summary, these results indicate that taurine has a protective effect on thiram-induced broilers and it can enhance the growth activity by directly affecting the development of chondrocytes and blood vessels.